Assessing the financial reporting practices of micro enterprises in Mizoram (International Journal of Food and Nutritional Sciences, 2022)
The main aim of this research is to generate an insight on the financial reporting practices of the Micro enterprises in Mizoram. It was also aimed at determining the accounting records kept by the micro enterprises as well as the purpose of maintaining accounting records. To achieve the research objectives, a structured questionnaire was developed containing open ended and close ended questions. Primary data were collected using Purposive Random Sampling techniques from 200 respondents, 100 each respondent from manufacturing sector and servicing sector. Percentages and frequency tables were the main medium used for analyzing the collected data with Statistical Package of Social Sciences (SPSS 22.0).